Weapon exports and aid to developing countries - Bruno S. Frey (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1973)
The goal of the rich countries should be to aid the poor countries to increase their standard of living but not to increase their holding of weapons. It is shown that a basic conflict of goals arises. The structure of consumption of the recipient countries cannot be influenced by giving the aid in the form of (civilian) goods in contrast to, the transfer of untied foreign exchange. In any case there results a substitution towards the bundle of commodities desired by the developing countries. Compared to that situation, the consumption of civilian goods can be induced to increase by granting a price-subsidy which, however, leads to a smaller increase in. utility than with a transfer in money or kind. Transfers of goods with restricted substitutability and all-or-none schemes are suggested to overcome the conflicts mentioned but they are most difficult to put into practice. To be effective, they imply an interference with the internal affairs of the poor countries which is per se undesirable. The paper suggests .that much more thought should be given to this important problem which is only rarely explicitely considered but which is most difficult to solve.
Keywords: 330